Curcumin: preventive and therapeutic properties in laboratory studies and clinical trials. - Strimpakos, A; Sharma, R (2008)
Curcumin is a natural polyphenol used in ancient Asian medicine. Since the first article referring to the use of curcumin to treat human disease was published in The Lancet in 1937, >2,600 research studies using curcumin or turmeric have been published in English language journals. The mechanisms implicated in the inhibition of tumorigenesis by curcumin are diverse and appear to involve a combination of antiinflammatory, antioxidant, immunomodulatory, proapoptotic, and antiangiogenic properties via pleiotropic effects on genes and cell-signaling pathways at multiple levels. The potentially adverse sequelae of curcumin's effects on proapoptotic genes, particularly p53, represent a cause for current debate. When curcumin is combined with some cytotoxic drugs or certain other diet-derived polyphenols, synergistic effects have been demonstrated. Although curcumin's low systemic bioavailability after oral dosing may limit access of sufficient concentrations for pharmacologic effects in tissues outside the gastrointestinal tract, chemical analogues and novel delivery methods are in preclinical development to overcome this barrier. This article provides an overview of the extensive published literature on the use of curcumin as a therapy for malignant and inflammatory diseases and its potential use in the treatment of degenerative neurologic diseases, cystic fibrosis, and cardiovascular diseases. Despite the breadth of the coverage, particular emphasis is placed on the prevention and treatment of human cancers.